VISUALIZATION AND QUANTITATIVE CHARACTERIZATION OF SMALL OBJECTS IN A LENS ACOUSTIC MICROSCOPE WITH A TWO-DIMENSIONAL ARRAY - S. A. Titov; A. N. Bogachenkov (Российский технологический журнал, 2018)
Application of a lens multi-element acoustic microscope for the visualization and quantitative characterization of small discontinuities with dimensions of the spatial resolution level is considered. On the basis of the paraxial approximation it was found that the recorded spatio-temporal signal of the microscope ultrasonic array can be treated as an estimation of the scattering function of visualized objects. It was theoretically established that the scattering functions of the observed inhomogeneities can be used for the interpretation of the generated acoustic images. It is shown that the finite size of the array elements constrains the angular resolution of the method due to smoothing of the measured scattering function. Experimental testing of the proposed method was carried out using the developed prototype microscope with a two-dimensional array of square elements and a polystyrene spherical acoustic lens. It was experimentally confirmed that the spatial resolution of the device corresponds to a theoretical estimate obtained by a classical criterion. The generated images of small flat reflectors with different angles of inclination obtained by means of electronic scanning are presented. It is shown that the output array data set is more informative for the quantitative characterization of the discontinuities than their acoustical images. In particular, on the basis of the obtained estimation of the scattering function it was possible to estimate the angle of inclination of the reflectors.